HYDROTHERMAL PRETREATMENT OF EMPTY FRUIT BUNCHES FOR THE POTENTIAL PRODUCTION OF ETHANOL. - MOHD SAMAN, SITI 'AISYAH (2014)
In general, lignocellulosic biomass contains three major components, namely lignin, hemicellulose and cellulose which are the polymers of C5 and C6 sugars. Thus, there is potential to utilize of this biomass for bioethanol production. The hydrolysis of cellulose into glucose was difficult due to the more fibrous nature and thus inhibits enzyme penetration into the cellulose. In order to solve this problem, hydrothermal pretreatment can be used for breaking the bonds within the lignin structure and increase the accessibility of enzyme into the cellulose. In this study, the works has been conducted in two different stages, e.g. ethanol production and glucose optimization. Separate hydrolysis and fermentation (SHF) is the common process in producing ethanol from lignocellulosic biomass. Nowadays, simultaneous saccharification and fermentation (SSF) process has been seen as potential process for producing ethanol with shortens process time with higher yield of ethanol.